2016
DOI: 10.1017/cjn.2016.87
|View full text |Cite
|
Sign up to set email alerts
|

E.03 Use of intra-arterial milrinone rescue therapy in patients with refractory and super refractory vasospasm after aneurysmal subarachnoid hemorrhage

Abstract: Background: Vasospasm causing delayed ischemic neurologic deficit (DIND) remains a leading cause of devastating outcome after aneurysmal subarachnoid hemorrhage (aSAH). Therapy using intravenous milrinone (IVM) and intra-arterial milrinone (IAM) has been described. We report our results using IAM in patients with refractory and super refractory vasospasm (RV and SRV respectively). Methods: Retrospective single center study of all adult patients treated with IAM between 2006 and 2016 inclusively. IAM was used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Functional neurological status can be ascertained by means of established scales (mRS, GOS) or by detailed follow-up neurological examination (usually at 3 and 6 months), and is usually described as “good” or “bad.” A total of 9 studies including 632 patients reported mRS scores 18 , 20 - 21 , 28 - 33 and GOS scores 14 , 27 in patients with DCI treated with milrinone, with follow-up times that varied from “at discharge” to a mean of 44.6 months. Good outcomes (mRS≤2 or GOS≥4) were seen in 57-82% of patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional neurological status can be ascertained by means of established scales (mRS, GOS) or by detailed follow-up neurological examination (usually at 3 and 6 months), and is usually described as “good” or “bad.” A total of 9 studies including 632 patients reported mRS scores 18 , 20 - 21 , 28 - 33 and GOS scores 14 , 27 in patients with DCI treated with milrinone, with follow-up times that varied from “at discharge” to a mean of 44.6 months. Good outcomes (mRS≤2 or GOS≥4) were seen in 57-82% of patients.…”
Section: Resultsmentioning
confidence: 99%
“…Measured outcomes and follow-up times were also very diverse: angiographic response, 14 - 21 Neurological exam, 13 , 17 , 22 - 26 Glasgow Outcome scale (GOS), 27 modified Rankin Scale (mRS), 18 , 20 , 21 , 28 - 33 cerebral infarction, 31 Barthel index, 28 and TCD values 34 35 In 7 studies only data on immediate results were available, 14 , 15 , 17 , 19 , 23 , 34 , 35 and in one publication the follow-up time was not specified 24 .…”
Section: Resultsmentioning
confidence: 99%
“…Recent retrospective series reported that an intra‐arterial milrinone treatment with angiography is safe and effective to reduce refractory VSP after SAH . Important to notice though, that in these studies, patients who did not recover from the coma status were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Milrinone is an inhibitor of phosphodiesterase III, with positive inotropic and vasodilatory effects . Although intra‐arterial milrinone contributes to the reduction of VSP, this usually requires concomitant use of angiography . On the other hand, its intravenous use is not well known and further studies are needed to assess this option, supported by bedside monitoring to guarantee the safety and effectiveness of the treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation